Towards Cultural Echology - Vikman, Noora; Rainio, Riitta (CCSP Press, Simon Fraser University, 2024)
In this article, we introduce some of the first steps taken in a new research project called "Sacred Sound and Ritual Soundscapes in Historical and Contemporary Fennoscandia: Acoustic Measurements, Ethnographic Research and Foundations for Cultural Echology". It proposes that sound waves projecting from environmental interfaces are far from being insignificant background elements, but active parts of the environment and our relationship with it. The new project will trace practices related to acoustics from the history of Fennoscandia, primarily from Finnish and indigenous Sámi traditions comparing the larger Finno-Ugric heritage also to the west of Fennoscandia, namely Norway. Practically, the study concentrates on acoustic measurements in echoing spaces in natural settings. We are interested in specific spaces, the use of them in collective rituals and events as well as more private encounters. Ethnographic participatory methods are used to be able to describe people’s relationship with their historical, cultural and more-than-human elements and environments. This article gives examples of the testimonies of two persons interviewed. In the footsteps of acoustic ecology, listening and sensing are considered important skills and activities. The cultural echology approach, then also looks for possibilities that may activate more lively and conscious “echological transformations”. Peer reviewed